Eliminating reverse water gas shift reaction in CO2 hydrogenation to primary oxygenates over MFI-type zeolite supported Cu/ZnO nanocatalysts - Ayodele, O.B. (Elsevier Ltd, 2017)
This study reports the synthesis of Cu/ZnO supported on Al2O3, SiO2, ZrO2 and solid acid catalyst ZSM-5 for the hydrogenation of CO2 to methanol (MeOH). The activity of all the supported catalysts except Cu/ZnO supported on ZSM-5 (CZZSM) tested at 250 °C and 2.25 MPa for 13 h time-on-stream (TOS) showed carbon monoxide as byproduct due to the nefarious reverse water gas shift reaction (RWGS) that typically compete with MeOH production during CO2 hydrogenation. Methyl formate and dimethyl ether which are value added specialty chemicals were the byproducts when CZZSM was tested and their production mechanism was ascribed to the acidity of the ZSM-5 support. According to the NH3-TPD and CO2-TPD studies, CZZSM has considerable acidity of 15.02 μmol/m2 which is about 20 folds higher than the 0.74 μmol/m2 measured for the basic sites. Furthermore, the extreme high resolution scanning electron microscopy (XHR-SEM) and BET results showed that the ZSM-5 framework, structural and textural properties were retained after the synthesis of CZZSM which showed that the synthesis protocol was expedient. Thus, the effect of the solid acid catalyst was easily evaluated. In addition, the XHR-SEM, TEM and XRD results showed that the Co-oxide particles were highly dispersed nano-particle with average size of 2.4 nm. The CZZSM achieved and impressive CO2 conversion of 20.25 with average space-time yield of 60 and 16 gproduct gcat -1 min-1, and selectivity of 77.70 and 10.0 for MeOH and MeF, respectively which are promising for industrial application. © 2017 Elsevier Ltd.